Arginine alleviates Clostridium perfringens α toxin-induced intestinal injury in vivo and in vitro via the SLC38A9/mTORC1 pathway - Wang, Xiaohui; Zhang, Tong; Li, Wenli; Wang, Heliang; Yan, Lei; Zhang, Xiaowen; Zhao, Lianwen; Wang, Nianxue; Zhang, Beibei (Frontiers in Immunology, 2024)
Clostridium perfringens α toxin is a main virulence factor responsible for gut damage in animals. Arginine is a functional amino acid exhibiting significant immunoregulatory activities. However, the effects and immunoregulatory mechanisms of arginine supplementation on α toxin-induced intestinal injury remain unclear. In vivo, 256 male Arbor Acres chickens were randomly assigned to a 2×2 factorial arrangement, involving diet treatments (with or without 0.3% arginine supplementation) and immunological stress (with or without α toxin challenge). In vitro, IEC-6 cells were treated with or without arginine in the presence or absence of α toxin. Moreover, IEC-6 cells were transfected with siRNA targeting mTOR and SLC38A9 to explore the underlying mechanisms. The results showed that in vivo, arginine supplementation significantly alleviated the α toxin-induced growth performance impairment, decreases in serum immunoglobulin (Ig)A and IgG levels, and intestinal morphology damage. Arginine supplementation also significantly reduced the α toxin-induced increase in jejunal proinflammatory cytokines interleukin (IL)-1β, IL-6 and IL-17 mRNA expression. Clostridium perfringens α toxin significantly decreased jejunal mechanistic target of rapamycin (mTOR) and solute carrier family 38 member 9 (SLC38A9) mRNA expression, while arginine supplementation significantly increased mTOR and SLC38A9 mRNA expression. In vitro, arginine pretreatment mitigated the α toxin-induced decrease in cell viability and the increase in cytotoxicity and apoptosis. Arginine pretreatment also alleviated the α toxin-induced upregulation of mRNA expression of inflammation-related cytokines IL-6, C-X-C motif chemokine ligand (CXCL)10, CXCL11 and transforming growth factor-β (TGF-β), as well as apoptosis-related genes B-cell lymphoma-2 associated X protein (Bax), B-cell lymphoma-2 (Bcl-2), B-cell lymphoma-extra large (Bcl-XL) and cysteinyl aspartate specific proteinase 3 (Caspase-3) and the ratio of Bax to Bcl-2. Arginine pretreatment significantly increased the α toxin-induced decrease in mTOR, SLC38A9, eukaryotic translation initiation factor 4E (eIF4E)-binding protein 1 (4EBP1) and ribosomal protein S6 kinase (S6K) mRNA expression. Knockdown SLC38A9 and mTOR largely abrogated the positive effects of arginine pretreatment on α toxin-induced intracellular changes. Furthermore, SLC38A9 silencing abolished the increased mTOR mRNA expression caused by arginine pretreatment. In conclusion, arginine administration attenuated α toxin-induced intestinal injury in vivo and in vitro, which could be associated with the downregulation of inflammation via regulating SLC38A9/mTORC1 pathway.